Comparative Chemical Properties Analysis of Nanobubble-Treated Gold Mine Tailings from Amalgamation and Cyanidation: Analisis Komparatif Sifat Kimia Tailing Tambang Emas Hasil Perlakuan Nanobubble dari Proses Amalgamasi dan Sianidasi - Nur Adibah, Nailah; Nurcholis, Mohammad; Rhazista Noviardi, Raden (Universitas Pembangunan Nasional Veteran Yogyakarta, 2025)
Tailings, the waste residue from gold mining processes, typically contain hazardous heavy metals that have the potential to contaminate the environment, particularly soil. This study aims to evaluate the changes in the chemical properties of gold mine tailings following nanobubble flotation treatment as an initial step toward sustainable remediation. Tailings samples were collected in a composite from two mining sites using different processing methods: cyanidation (GMBU Antam Pongkor, Bogor) and amalgamation (ASGM Kertajaya, Sukabumi). Nanobubble flotation was applied using combinations of reagents consisting of collectors (EDTA or NaOH), a frother (MIBC), and depressants (Na₂SiO₃ or Na₂CO₃). Parameters analyzed included pH (H₂O, KCl, H₂O₂), Cation Exchange Capacity (CEC), and exchangeable base cations (Ca, Mg, K, Na), measured using standard soil chemical methods. Comparative analysis was performed to assess changes in tailings chemistry before and after treatment. Results showed that nanobubble flotation slightly increased the pH of both tailings, indicating the neutralization of residual acidity. Varied CEC values depending on reagent composition, reflecting differences in the interaction between reagents and clay mineral surfaces. Base saturation in both sites remained low, suggesting that additional amelioration, such as gypsum or organic matter, is still required to improve cation balance. Nanobubble technology affected the tolerated tailings’ chemical properties for soil and plants and demonstrated potential as a preliminary step toward the reclamation and reutilization of gold mine tailings for future land use.